ABOUT DIDACTIC BOUNDARIES OF SPANISH-PORTUGUESE FALSE FRIENDS - Carballido, Xurxo Fernández (2019)
The so-called false friends are a very frequent question in the works on the relationship between Portuguese and Spanish language. The possible approaches change according to the interests and the focus: lexicography, lexicography, semantics, traductology or foreign languages teaching. This article aims to be a contribution but it does not want to compile or classify false friends, but to establish some limits on the educational use of false friends.